Instrumenty wsparcia finansowego krajów partnerskich w ramach Europejskiej Polityki Sąsiedztwa - Kalicka-Mikołajczyk, Adriana (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The European Neighbourhood and Partnership Instrument ENPI is the financial instrument for the European Neighbourhood Policy. It aims at supporting the achievement of the objectives of the European Neighbourhood Policy ENP with a view to establishing an area of prosperity and good neighbourhood relations between and with ENP partner countries and Russia. It is addressed to ENP partner countries including Russia and offers co-funding for promoting good governance and equitable social and economic development process. The budget for the ENPI amounts to 11,181 million euro for the period 2007–2013, 95% of which is for national and multi-country programmes and 5% for cross-border cooperation programmes. For the period 2014–2020, the ENPI will be succeeded by a New European Neighbourhood Instrument ENI. This new financial instrument will have a budget of around € 15.4 billion. The ENI will build on and strengthen some of the key features of the ENPI, notably greater differentiation between countries based on progress with reforms and two new mechanisms to support an incentive-based approach often referred to as “more for more.” Under the ENI, four types of programme are supported: bilateral programmes for the neighbourhood countries; regional programmes for the East and the South; an ENP-wide programme mainly funding Erasmus for All and the Neighbourhood Investment Facility and finaly cross-border co-operation programmes between Member States and neighbourhood countries.
Keywords: Unia Europejska; Europejska Polityka Sąsiedztwa; Europejski Instrument Sąsiedztwa i Partnerstwa; TACIS; MEDA